Comparison between Special Judo Fitness Test, metabolic variables and energy contribution in young judo athletes - Foresti, Y.; Bertucci, D.; de Carvalho, C.; Kalva-Filho, C.; de Andrade, V.; Barbieri, R.; Bonagambas, T.; Papoti, M. (Archives of Budo, 2020)
Background and Study Aim: Judo has been characterized as a high-intensity intermittent combat sport. The study's purpose is answer the question whether Special Judo Fitness Test (SJFT) variables are capable of discriminate young judo athlete`s performance at different ages, and comparing the test with metabolic indicators and energy contribution.